Minocycline resistance in an oral Streptococcus infantis isolate is encoded by tet(S) on a novel small, low copy number plasmid. Issue 2 (19th March 2014) - Ciric, Lena; Brouwer, Michael S. M.; Mullany, Peter; Roberts, Adam P.
Abstract We have determined the genetic basis of minocycline resistance in a strain of Streptococcus infantis isolated from a healthy human oral cavity. We demonstrate that tet(S), identical to tet(S) found on the enterococcal conjugative transposon Tn6000, is responsible for the observed resistance. The gene is located on a small, low copy number plasmid and is flanked by IS1216 elements. The tet(S) gene is capable of excising from the plasmid together with one of the IS1216 elements. The plasmid contains a putative toxin/antitoxin system related to relBE. Deletion of the toxin, relE, did not result in plasmid instability but did increase the fitness of the mutant compared to the wild‐type strain.